1278. Testing the Synergistic Effect of Ceftazidime-Avibactam Plus Aztreonam on Metallobetalactamase-Producing Non-Fermenting Gram-negative Bacteria. (4th December 2021) - Crouch, Elena M; Johnson, Sheila; Bennett, Jason
Abstract: Background: Metallo-betalactamases (MBL) are rapidly becoming a more widespread form of antimicrobial resistance. MBL are class B betalactamases that use zinc rather than serine in their active site and are only inactivated by monobactams, such as aztreonam. Unfortunately, most MBL-producing organisms also produce aztreonam-inactivating beta-lactamases. Synergy between ceftazidime-avibactam and aztreonam is well documented for MBL-producing Enterobacteriaceae but has not been tested extensively in non-fermenting Gram-negative bacteria. This study evaluates the susceptibilities of non-fermenting Gram-negative bacteria via E-test to this combination in vitro, in order to provide support for use to treat infections from these organisms. Methods: The antibiotic combination ceftazidime-avibactam+aztreonam was tested against a total of 33 isolates, including MBL-producing Pseudomonas aeruginosa, Pseudomonas putida, and the intrinsically aztreonam resistant Acinetobacter baumanii using the E-test method. MBL-producing Enterobacteriaceae were included as positive controls. All isolates were also tested against ceftazidime alone, aztreonam alone, and ceftazidime-avibactam. Bacterial isolates were procured from the Multidrug-resistant organism Repository & Surveillance Network at the Walter Reed Army Institute of Research. Antimicrobial resistance genes were previously identified by whole genome sequencing Results: Of 13 Pseudomonas spp. isolates tested, 9 were resistant, 3 were intermediate, and 1 was susceptible to aztreonam. Synergistic testing of ceftazidime-avibactam+aztreonam reduced the MIC of 4 Pseudomonas isolates by 1-2 doubling dilutions. While Acinetobacter spp. are usually considered intrinsically resistant to aztreonam, synergistic testing of ceftazidime-avibactam+aztreonam reduced the MIC of all 12 isolates tested by 1 to 3 doubling dilutions. Conclusion: The ability of ceftazidime-avibactam+aztreonam to reduce the MICs of Acinetobacter baumanii and MBL-producing Pseudomonas aeruginosa is a potentially promising therapeutic option when faced with growing antimicrobial resistance. Disclosures: All Authors : No reported disclosures